Effect of water deficits and season on berry development and composition of Cabernet Sauvignon (Vitis vinifera L.) grown in a hot climate. (27th April 2017) - Cooley, N.M.; Clingeleffer, P.R.; Walker, R.R.
Abstract: Background and Aims: The effect of season and deficit irrigation treatments was monitored on berry development and composition, yield and wine composition of Vitis vinifera L. cv. Cabernet Sauvignon grown in a hot climate during 2003–2005. Methods and Results: The treatments were regulated deficit irrigation (RDI) and prolonged deficit irrigation (PD), compared with a standard industry irrigation (Control) treatment. Compared to the Control, RDI berries were smaller from a reduction in mesocarp (flesh) rather than in exocarp (skin) or seed mass but insufficient to significantly impact on yield. The PD treatment reduced berry size driven by mesocarp reduction resulting in a lower yield. Season 2005 had a significantly larger yield, mainly as a result of increased berry fresh mass, exocarp and seed mass compared to that of either 2003 or 2004. Grape juice TSS and pH were not significantly affected by water deficit, but each varied between seasons. The malic acid concentration of grape juice was reduced by the RDI and PD treatments, resulting in enhancement of the tartaric : malic acid ratio. Grape anthocyanin at harvest was unaffected by irrigation treatment but significantly impacted by season. Wine colour density, anthocyanin, ionised anthocyanin and phenolic substances were increased by RDI and PD and impacted by season. Conclusions: Wine attributes were improved further by PD relative to RDI. Seasonal effects were shown to have an impact greater than the within‐season water deficit treatments on most aspects of berry development and composition. Significance of the Study: The study has demonstrated the utility of the PD treatment as an irrigation tool, where water availability is significantly limited and/or where improved spectral properties are required for wines.